MORE THAN JUST A RACING HEART: PALPITATIONS UNCOVER HYPERTROPHIC CARDIOMYOPATHY IN ATHLETES - Sebastian Rurka; Jan Kamiński; Julia Dolinkiewicz; Agnieszka Szczerbińska (International Journal of Innovative Technologies in Social Science, 2025)
Heart palpitations are a common symptom reported by athletes presenting to sports medicine clinics and cardiology departments. While often benign, palpitations in this population can indicate underlying structural heart disease, notably hypertrophic cardiomyopathy, which is a leading cause of sudden cardiac death in young athletes.Methods: This narrative review was conducted using PubMed and Google Scholar, focusing on studies published between 2016 and 2024. Standard textbooks in cardiology and internal medicine were also consulted to ensure comprehensive coverage of current knowledge.Results: The analysis showed that palpitations can result from both mild and severe arrhythmias and structural heart disease. The importance of differential diagnosis and the role of imaging studies and ECGs in identifying the cause was emphasized. Special attention was paid to hypertrophic cardiomyopathy as a common genetic cause of symptoms. The need for an individualized therapeutic approach and patient education was also pointed out.Conclusions: Palpitations in athletes should never be overlooked, as they may be the first sign of hypertrophic cardiomyopathy, a potentially life-threatening condition.. Special attention should be paid to hypertrophic cardiomyopathy, which is a common genetic cause of cardiac arrhythmias. Diagnosis should be based on careful differentiation of causes and the use of imaging studies and ECGs. Successful management requires an individualized therapeutic approach and patient education in recognizing and responding to symptoms.